Crystallization and preliminary X‐ray characterization of the tetrapyrrole‐biosynthetic enzyme porphobilinogen deaminase from Bacillus megaterium. Issue 8 (31st July 2013) - Azim, N.; Deery, E.; Warren, M. J.; Erskine, P.; Cooper, J. B.; Wood, S. P.; Akhtar, M.
<x xml:space="preserve">Abstract</x> The enzyme porphobilinogen deaminase (PBGD; hydroxymethylbilane synthase; EC 2.5.1.61) catalyses an early step of the tetrapyrrole‐biosynthesis pathway in which four molecules of the monopyrrole porphobilinogen are condensed to form a linear tetrapyrrole. The enzyme possesses a dipyrromethane cofactor which is covalently linked by a thioether bridge to an invariant cysteine residue. Expression in Escherichia coli of a His‐tagged form of Bacillus megaterium PBGD permitted the crystallization and preliminary X‐ray analysis of the enzyme from this species at high resolution.